Displacement response of a concrete arch dam to seasonal temperature fluctuations and reservoir level rise during the first filling period: evidence from geodetic data - Yigit, Cemal Ozer; Alcay, S.; Ceylan, A. (2016)
© 2015 Taylor & Francis. The present study evaluates the dynamic behaviour of the Ermenek Dam, the second highest dam in Turkey, based on conventional geodetic measurements and Finite Element Model (FEM) analyses during its first filling period. In total, eight periods of measured deformation are considered from the end of construction until the reservoir reached its full capacity. The displacement response of the dam to the reservoir level and to seasonal temperature variations is examined in detail. Time series of apparent total displacements at the middle of the crest of the dam exhibits periodicity and linear trends. Correlation analysis revealed that periodic and linear displacement responses of the dam are related to variations of seasonal temperature and linearly increased reservoir level, respectively, indicating a relation between temperature, water load and dam deformation. It is also concluded that measured deformations based on geodetic data show good agreement with the predicted deformation obtained by the FEM analysis.